Azurin a potent anticancer and antimicrobial agent isolated from a novel Pseudomonas aeruginosa strain - Nourhan A. Zaghloul; Mona K. Gouda; Yasser Elbahloul; Nancy M. El Halfawy (Scientific Reports)
Abstract Azurin, a bacterial blue-copper protein, has garnered significant attention as a potential anticancer drug in recent years. Among twenty Pseudomonas aeruginosa isolates, we identified one isolate that demonstrated potent and remarkable azurin synthesis using the VITEK 2 system and 16S rRNA sequencing. The presence of the azurin gene was confirmed in the genomic DNA using specific oligonucleotide primers, and azurin expression was also detected in the synthesized cDNA, which revealed that the azurin expression is active. Furthermore, crude azurin protein was extracted, precipitated using 70% ammonium sulfate, dialyzed, and subjected to purification using carboxymethyl-Sephadex in affinity chromatography as a cheap method for purification. The partially purified azurin protein was characterized using polyacrylamide gel electrophoresis, energy-dispersive X-ray spectroscopy, Fourier-transform infrared spectroscopy, and nuclear magnetic resonance spectroscopy. Notably, qualitative elemental analysis by EDX showed the presence of copper and sulfur, corresponding to the copper-core and disulfide-bridge, respectively, in the purified azurin fraction. Moreover, FTIR spectroscopy revealed characteristic amide I and II absorption peaks (1500–1700 cm− 1), revealing the possible secondary structure of azurin. The results of NMR revealed the presence of characteristic amino acids such as methionine and cysteine, which confirmed the EDX results for sulfur-containing amino acids. Purified azurin exhibited antimicrobial activity against Staphylococcus aureus, Bacillus subtilis, Escherichia coli, and Klebsiella pneumoniae. Additionally, its anticancer properties were determined using the MTT assay and cell cycle analysis, revealing a preference for inhibiting the MCF7 breast cancer cell line where breast cancer is most common in Egypt. Overall, the research findings suggest that the local isolate, P. aeruginosa strain 105, could be a potential source of azurin protein for incorporation into cancer treatment strategies.